The Identitarians : The Movement against Globalism and Islam in Europe - Zúquete, Jose Pedro; Zúquete, Jose Pedro (Book collections on Project MUSE., 2018)
"This is a study of the contemporary European ultra-nationalist movement, in-depth. Zúquete studies the individuals, political parties, and broader trends to demonstrate the growing strength and alliances among these once disparate groups fighting against perceived Islamic encroachment and rising immigration. Zúquete also ties the European experience to the emerging American nationalist identity, culminating in their support of Trump and this year's public protests on university campuses"--.